SMART TOURISM DESTINATION MANAGEMENT IN KARANGASEM REGENCY OF INDONESIA - Sucipta G.N.K.; Utama M.S.; Dewi H.U.; Yuliarmi N.N. (Russian Journal of Agricultural and Socio-Economic Sciences, 2019)
The management of tourism destinations in Karangasem Regency has implemented smart tourism by utilizing information and communication technology to face competition in the tourism sector. This study aims to analyze the effect of human capital, social capital, entrepreneurship, implementation of information and communication technology on the performance of smart tourism destinations in Karangasem Regency, Bali. This research was conducted on 155 samples of tourism industry owners in five tourist destinations in Karangasem Regency. The data obtained were analyzed with structural model equations using the Partial Least Square (PLS) program package. This study found that human capital, social capital, entrepreneurship, implementation of information and communication technology had a positive and significant effect on the performance of smart tourism destinations in Karangasem Regency.